Proposta de atividades reflexivas para os desvios ortográficos do –r em coda final em formas verbais - Freitas, Érica Aparecida Alves Fraga (2018)
Written communication according to orthographic conventions might be important to practice a successful social interaction. For that, the Schools have a primordial role, as we expect that the student writes correctly, appropriating itself of the written code. However, most of the students, even that ones on High School, still can’t embrace how writing works, overwriting according to the speaking. Thus, the present research pursues to evaluate how a reflexive teaching affects written conventions of infinitive and the singular 3rd person of indicative present and orthographic deviates common at these verbal forms: the deletion of –r at final coda and its insertion as a grapheme. Thereunto, data was gathered based on produced texts for 7th grade students, registered at a public school at Fortaleza-Ceará. Developing the research-action, it were applied diagnose tests that show us the number of orthographic deviations studied. Considering these obtained results, interventive activities were elaborated to treat the issue in focus, based on studies of Morais (2008) and Nóbrega (2013). As a way to supply these difficulties, the activities were based on reflection and the use of norm objecting the significant learning of Elementary School. Post tests showed positive results, increasing error percentage of 27% of issues on pre test to 8% on post test. So, we may conclude that regular and planned orthographic activities, based on linguistic knowledge approaching the written language as a reflexive and productive way, generates positive results.